The application of Law No. 31298 and the infringement of labor rights acquired by service providers in public entities - Montalvo Santisteban, Rusbeyra Nataly (2023)
The purpose of this investigation is to analyze whether the application of Law No. 31298 results in the violation of the labor rights acquired by workers hired under the modality of location of services in the public sphere. Since the implementation of this norm, deadlines have been established for these workers to adapt and participate in public competitions based on merit, with the aim of accessing positions under the various labor regimes of the State. However, due to the open and public nature of these contests, there is no unequivocal guarantee of access to the positions, which could eventually lead to the termination of their contracts and, therefore, to the potential violation of their labor rights.